Gastropods from raised marine deposits along the Beagle Channel, southern Argentina: The ancestors of the living fauna - Zelaya, Diego Gabriel (2011)
This contribution focuses on the diversity of gastropods that lived in the Beagle Channel during the Early and Middle Holocene (from ca. 7500 to 4000 years BP). This temporal framework has special interest because it allowed us to evaluate the colonization process of a relatively recent marine ecosystem, the Beagle Channel (originated 8000-7500 years ago), and the possibility that this channel has represented a 'faunistic corridor' between the Atlantic and Pacific waters of the Magellan Region. Fossil material from four sampling localities was studied; 31 species of gastropods were identified. Additional records of four species of gastropods from six other sites at the Beagle Channel are provided. The fauna described in this work represents the ancestors of the living fauna in the region. In addition, most of these species are also currently found both in the Atlantic and Pacific Magellanic waters, strongly suggesting that the Beagle Channel represented a favourable route for the dispersal of molluscs.